Talent Management System pada Program Pengembangan Sumberdaya Manusia di SAKA Indonesia Pangkah Limited - Yuga Adi Kusuma (Universitas Darussalam Gontor, 2017)
The need for energy both oil and gas in the world and in Indonesia continuesto increase this condition is required the best energy management, ofcourse, supported by qualified human resources and good capacity, energymanagement will work well too. This study aims to determine the talentmanagement system program in the human resources developmentprogram in SAKA Indonesia Pangkah Limited. The results obtained, in theframework of talent management has not been fully running well, especiallyin the selection and recruitment process, still using the traditional way hasnot been using talent mapping. In the characteristics of talent managementSIPL has had development-oriented thinking, applied high work culture, talentmanagement system applied got support from management, and hasapplied good human resource information system. Suggestions can be givenis to provide the widest opportunity to the resources owned companies togrow, given the promotion or grade improvement to the talent of consistentperformance, and also provide rewards to the achievers and punishment to.the less consistent performance